Fostering Harmonious Communication Between Parents and Generation Z in the Era of Everyday English Usage: Community Service with Al Jannah Islamic Study Group Mothers at Musholla Babul Ihsan Bromo Street, Medan - Cici Handayani; Selfitrida A Yani; Sharina Amanda; Widy Hastuty (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The rapid advancement of communication technologies and the widespread penetration of digital culture have significantly accelerated the emergence of code-switching phenomena, characterized by the blending of Indonesian and English expressions in the daily communication practices of Generation Z. This linguistic trend has frequently contributed to communication gaps and emotional tensions between adolescents and parents, particularly those with limited digital literacy. This community service program aims to address these interpersonal communication barriers through a communicative da’wah-based approach, interactive lectures, lexical breakdown workshops (popular slang glossary), and dialog simulation (roleplay). The target partners of this program were the members of the Al Jannah Women’s Qur’anic Study Group at Musholla Babul Ihsan, Bromo Lorong Damai Street, Medan City. Using a descriptive qualitative method grounded in participatory observation and oral feedback analysis, this program examined changes in participants’ perspectives regarding the psycholinguistic dynamics of adolescents. The findings indicate that a humanistic, faith-based learning approach was effective in reducing parental emotional resistance, significantly improving modern vocabulary literacy, and fostering awareness of assertive parenting communication patterns. Following the intervention, participants demonstrated improved ability to interpret the emotional meanings embedded in adolescents’ contemporary expressions, thereby reducing potential emotional conflict within the family environment